Morphological Variations of the Sphenoid Sinus and Their Surgical Implications in Neurosurgery - Abdalla, Abuzar; Anwer, Danish; Awadlseid, Khalid Musa Fadlelmula; Fadoul Alhassen, Muntaser Mohammed; Ansari, Hamid (Journal of Neonatal Surgery, 2025)
Introduction: The sphenoid sinus exhibits complex morphological variations with significant implications for trans-sphenoidal neurosurgical approaches. This study aimed to characterize these variations in an Indian population and analyze their clinical implications for sellar and parasellar surgical approaches. Methods: A prospective observational study was conducted on 160 patients who underwent high-resolution CT scans at the Autonomous State Medical College, Kanpur Dehat, Uttar Pradesh, from January 2024 to December 2024. Pneumatization patterns, septation configurations, and relationships with adjacent neurovascular structures were systematically evaluated. Statistical analysis included descriptive statistics, chi-square tests, and logistic regression to identify predictors of anatomical variations. Results: Sellar pneumatization was predominant (61.3%), followed by presellar (20.6%), postsellar (12.5%), and conchal types (5.6%). Multiple septations were observed in 50.6% of cases, with 18.8% attached to the carotid protuberance. Internal carotid artery protrusion or dehiscence was identified in 25.6% of cases, with significantly higher prevalence in postsellar pneumatization (45.0%, p<0.001). The mean distance from sinus wall to internal carotid artery was 4.92±2.31mm, with minimum distances as low as 0.6mm. Significant age-related variations were observed, with increased pneumatization and neurovascular protrusions in older patients (p=0.021 and p=0.039, respectively). Conclusion: The high prevalence of sellar/postsellar pneumatization, multiple septations, and neurovascular protrusions in the Indian population necessitates meticulous preoperative assessment for transsphenoidal approaches. The significant correlations between pneumatization patterns and neurovascular relationships provide a framework for preoperative risk stratification, potentially improving surgical safety and outcomes in sellar and parasellar neurosurgery.